JURNAL KHUSUS AKUNTANSI PERUSAHAAN DAGANG - Widjaja , Djeni Indrajati (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
St. Kristoforus I Catholic High School in West Jakarta is a national private school that follows the 2013 curriculum standards from the Ministry of Education, Culture, Research and Technology. The economics subjects given for 1 semester include knowledge of general economics and accounting. It is felt that the introductory material about Accounting needs to be expanded to provide deeper insight for students who are interested in the field of accounting. This is closely related to students' interest in further studies and in preparing for their future after graduating from high school. An introduction to the world of accounting, specifically about transactions in trading companies with journals in particular, is an added value to students' self-confidence when continuing their education at universities in the economics faculty, especially accounting study programs. For this reason, this training activity as an extracurricular activity is held for students from class X to class XII who are interested.